Physical and functional interactions among AP-2 transcription factors, p300/CREB-binding protein, and CITED2. - Bragança, J; Eloranta, J; Bamforth, S; Ibbitt, J; Hurst, H; Bhattacharya, S (2003)
The transcriptional co-activators and histone acetyltransferases p300/CREB-binding protein (CBP) interact with CITED2, a transcription factor AP-2 (TFAP2) co-activator. p300/CBP, CITED2, and TFAP2A are essential for normal neural tube and cardiac development. Here we show that p300 and CBP co-activate TFAP2A in the presence of CITED2. TFAP2A transcriptional activity was modestly impaired in p300(+/-) and CBP(+/-) mouse embryonic fibroblasts; this was rescued by ectopic expression of p300/CBP. p300, TFAP2A, and endogenous CITED2 could be co-immunoprecipitated from transfected U2-OS cells indicating that they can interact physically in vivo. CITED2 interacted with the dimerization domain of TFAP2C, which is highly conserved in TFAP2A/B. In mammalian two-hybrid experiments, full-length p300 and TFAP2A interacted only when CITED2 was co-transfected. N-terminal residues of TFAP2A, containing the transactivation domain, are both necessary and sufficient for interaction with p300, and this interaction was independent of CITED2. Consistent with this, N-terminal residues of TFAP2A were required for p300- and CITED2-dependent co-activation. A histone acetyltransferase-deficient p300 mutant (D1399Y) did not co-activate TFAP2A and did not affect the expression or cellular localization of TFAP2A or CITED2. In mammalian two-hybrid experiments p300D1399Y failed to interact with TFAP2A, explaining, at least in part, its failure to function as a co-activator. Our results suggest a model wherein interactions among TFAP2A, CITED2, and p300/CBP are necessary for TFAP2A-mediated transcriptional activation and for normal neural tube and cardiac development.